3. Flies Larva On White Rat Carcass (Rattus norvegicus Berkenhout, 1769) With Various Treatment Outdoor - ichsan luqmana Indra Putra; Sadda Salisa Yahya (Jurnal Medika Veterinaria, 2021)
Insect activity including its life cycle can determine the estimated time of death or Post Mortem Interval (PMI). One type of insect that plays an important role in determining the estimated time of death is flies. This study aims to determine the types of flies that come to the carcass and to determine the types of flies that dominate and less dominate from each treatment onwhite rat (carcassesR. norvegicusmale) outdoors. This study consisted of 3 treatments with 3 repetitions each. The treatments included A (neck bone dislocation), B (burned), and C (poisoned). Carcass observations were carried out for 10 days and larvae collection was carried out every 2 days starting from the third day of observation. The parameters observed included the number and morphological characteristics of instar 3 fly larvae. The types of fly larvae found in all treatments were Lucilia illustris (5.42%), Sarcophaga sp (12.80%), Sarcophaga argyrostoma (30.62%), and Sarcophaga variegata (51.16%). The dominant fly larvae of the three treatments was S. variegata and the less dominant fly larvae was L. illustris.